PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH KUALITAS PRODUK, HARGA, PROMOSI, KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DI KFC KABUPATEN MIMIKA - Arunita Afria Azis; Nur Anisa Firda, Nurul Fhadilla .N. (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the role of customer satisfaction as a mediating variable in the influence of product quality, price, promotion, and service quality on customer loyalty at KFC Mimika Regency. A quantitative approach is used in this study, with data collection through questionnaires distributed to KFC customers. The independent variables are product quality, price, promotion, and service quality, while the dependent variable is customer loyalty, and the line variable is customer satisfaction. The method used in this study is the associative method and the path method. The sample used was 50 respondents using documentation techniques, namely the distribution of questionnaires distributed to KFC customers. The data source used in this study is quantitative data, namely testing the relationship or influence between variables. The results of this study prove partially that the variables of product quality, price, promotion, service quality have an influence on customer loyalty. And also the variables of product quality, price, promotion, service quality have an influence on customer satisfaction through customer loyalty.